Causal relationship between non-alcoholic fatty liver disease and sarcopenia: a bidirectional Mendelian randomization study - Chen, Meng; Liu, Jili; Xia, Xin; Wang, Yarong; Zheng, Hongying (Frontiers in Medicine, 2024)
Introduction: A correlation between non-alcoholic fatty liver disease and sarcopenia is demonstrated, but the causality remains unclear. Our study aims to clarify the point of genetics between non-alcoholic fatty liver disease (NAFLD) and sarcopenia at the level of gene prediction through two-sample Mendelian randomization (MR) analysis.The study employed the two-sample MR approach to investigate the bidirectional causality between NAFLD and sarcopenia. Published summary statistics were used to obtain instrumental variables (IVs) at the genome-wide significance level. Results: IVW analysis showed that the risk of NAFLD was reduced when walking pace was increased (OR=0.435, 95%CI 0.240-0.789, P=0.006); Increasing appendicular lean mass(ALM) decreased the risk of NAFLD(OR=0.906, 95%CI 0.838-0.980, P=0.014); Those older than 60 were more likely to suffer from NAFLD if they had low grip strength(OR=1.411, 95%CI 1.087-1.830, P=0.0012). In the reverse MR study, weight median analysis showed that NAFLD caused a decrease in ALM (OR=0.953, 95%CI 0.957-0.994, P=0.001); whereas NAFLD showed no correlation with usual walking pace or grip strength (all with P>0.05). MR-Egger regression analysis showed that there was no horizontal pleiotropy in the SNPs (all with P>0.05). Conclusion: The characteristics related to sarcopenia (Usual walking pace, appendicular lean mass and low hand grip strength) may play a causal role in the development of nonalcoholic fatty liver disease, although the underlying mechanisms need to be further investigated. The presence of specific single nucleotide polymorphisms (SNPs) such as rs3747207, rs429358, and rs73001065 has been identified in the PNPLA3, APOE, and MAU2 proteins. These genetic markers represent potential targets for future interventions aimed at addressing, managing, or mitigating the risk of NAFLD.